Stable Mode-Locked Operation With High Temperature Characteristics of a Two-Section InGaAs/GaAs Double Quantum Wells Laser - Zhongliang Qiao (IEEE Access, 2021)
A monolithic two-section InGaAs/GaAs double quantum wells (DQWs) mode-locked laser (MLL) emitting at 1.06 μm is demonstrated. Stable mode locking operation is achieved up to 80 °C. The fundamental repetition rate is at ~9.51 GHz with a signal-to-noise ratio (SNR) of more than 55 dB, and up to the fourth harmonic at ~38.04 GHz is observed. The characteristic temperature (T0) of the laser and the influences of absorber bias voltage on T0 have been systematically investigated. From our findings, T0 shows a two-segment feature, and is slightly affected by the absorber bias voltage for photon saturation.